CORRELATION BETWEEN SELF-CARE BEHAVIORS, FAMILY RELATIONSHIP, AND HAPPINESS OF THE ELDERLY AT THE COMMUNITY SAIMAI DESTRICT - บูรณกลัศ, วัลภา (JOURNAL OF THE POLICE NURSES AND HEALTH SCIENCE, 2017)
The objectives of this research were to studies: 1) the self-care behavior of the elderly, 2) the family relationship of the elderly, 3) the happiness of the elderly, and 4) the correlation between the self-care behavior, family relationship, and happiness of the elderly. The samples were 60 years ago and upper, amount 70 older persons at the community Saimai destrict in Bangkok metropolitan. The instrument of this research was general information questionnaire, the self-care behavior questionnaire, the family relationship questionnaire, the happiness questionnaire. Data were analyzed by frequency, percentage, mean, standard deviation, and Pearson product-moment correlation analysis. The results of study were as follows: 1) the level of self-care behavior of the elderly at the community Saimai destrict in Bangkok metropolitan were high; 2) the level of family relationship of the elderly at the community Saimai destrict in Bangkok metropolitan were high; 3) the level of happiness of the elderly at the community Saimai destrict in Bangkok Metropolitan were extremely high; and 4) there were significantly positive correlation between self-care behavior, family relationship, and happiness of the elderly at the community Saimai destrict in Bangkok metropolitan at .01 level and significantly positive correlation between self-care behavior and family relationship of the elderly at the community Saimai destrict in Bangkok metropolitan at .01 level.